(untitled) (Italian Journal of Public Health, 2005)
Dear Sir, Chronic-degenerative diseases (CDD), including atherosclerosis, cancer and chronic-obstructive pulmonary diseases, are the main causes of death in developed countries, accounting for approximately 90% of mortality. These pathologies arise from a complex network of risk-factors both exogenous and endogenous in origin. The role of preventive medicine in counteracting this major public-health problem is pivotal, especially since treatment of these diseases is difficult. The goal of preventive medicine is to shed light on the network of CDDrelated risk factors in healthy subjects, thus allowing for primary preventive interventions aimed at removing harmful exposures, increasing host-defence mechanisms and activating targeted early-screening programs in susceptible individuals.CDD risk-factors are identified by anamnestic evaluation and questionnaires as well as chemical-laboratory analyses and the clinical examination of patients. For example, the risk assessment for atherosclerosis is performed by analysing diet and smoke-exposure habits, measuring blood pressure, lipid profile, etc., however, a similar approach may only in part be pursued for cancer because the majority of the related pathogenic phenomena occurs at molecular level.